Matharpacady-10.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Marian Villa is among the better-preserved Portuguese-style bungalows in Matharpacady, home to the Mascarenhas family. Azulejo tiles are used for the nameplate, similar to those used in Goan homes. Arabic in origin, these blue and white tiles were produced by the Spanish from the 14th century onward to decorate their churches and monasteries. The Portuguese imported the tiles from Spain and, in the 17th century, started exporting them to their colonies, from where they reached Goa.